Strategi Implementasi Pendidikan Agama melalui Metode Pendekatan Berbasis Pendidikan Multikultural - Andika, Nursidik Jaka; Harmita, Harmita; Banggiok, Revandika S.; Muhyidin, Muhyidin (TSAQOFAH, 2022)
This study aims to find out how to implement multiculturalism in an Islamic religious education and is oriented to strategies and opportunities. The method used is a qualitative approach with literature searches and various insights and developments. This type of research is qualitative, namely by conducting various literature searches and various insights and developments. The use of this qualitative method is because in this study it is to reveal and understand something about the implementation of religious education through a multicultural approach with strategies and opportunities. Important strategies and opportunities are a concern so that the implementation of Islamic religious education through a multicultural approach can run well. The role of strategy and opportunity is also very important, namely in order to be able to manage a system as a whole by maximizing the existing potential and actions to be taken in implementing Islamic religious education using a multicultural approach.